(untitled) (Eurasian Journal of Engineering and Technology, 2022)
This paper presents the results of an experimental and analytical study of the abrasive aggressiveness of dust particles present in fuels and engine oils of automobile engines. Because the wear of parts of the cylinder-piston group is mainly abrasive in nature, the abrasive ability of dust particles of engine fuel pollution was studied. The study found that it depends on the logarithmic-normal distribution of dust particles and the numerical values of their abrasive aggressiveness, which significantly facilitates the development of theoretical issues to reduce the breakdown of engine parts